International Humanitarian Law Handbook for Parliamentarians N° 25 - Kareen Jabre and Norah Babic (IPU), Antoine Bouvier (ICRC) (2016)
This kit aims to assist members of parliament to oversee national progress and investments made towards achieving the Millennium Development Goals in their country, using disaster risk reduction. Goal by goal, it outlines priorities, steps and interventions needed to reduce or eliminate disaster risks. And, of course, this kit gives examples of the good work already done by many parliaments around the world.